Deconstructing home-based care for mental illness: Can one identify the effective ingredients? - Burns, T; Catty, J; Wright, C (2006)
Objective: Home-based care for severe mental illness has been the focus of intense research over the last 30 years and has produced mixed results. Replications of Assertive Community Treatment (ACT) in Europe have consistently failed to find these differences and various explanations have been advanced for this. Method: Studies were compared in context of health care, and then identifying and rating the components of the differing teams rather than simply their designation. Cluster analysis was used for the identification of common service characteristics and regression analysis to test for correlation with reduction in hospitalization. Results: The nature of the control service may significantly explain the international variation in results. Six regularly occurring features of experimental services were identified from the examination of the components - smaller case loads, regularly visiting at home, a high percentage of contacts at home, responsibility for health and social care, multidisciplinary teams and a psychiatrist integrated in the team. Two of these, regularly visiting at home and responsibility for health and social care, are significantly associated with a reduction in hospitalization. Conclusions: It is premature to define an optimal configuration for home based care services. The need for introducing differing components of such care will depend on what is currently available locally. Where regular home visiting to psychotic patients plus a broad service model incorporating health and social care objectives are provided, major reductions in in-patient care are not currently to be anticipated by service reconfigurations. © 2006 Blackwell Munksgaard.